A 177 Years Extended of Teak Chronology Revealing to the Climate Variability in Phrae Province, Northern of Thailand - Kanokrat Buareal; Supaporn Buajan; Sineenart Preechamart; Chotika Muangsong; Nathsuda Pumijumnong (Applied Environmental Research, 2020)
Teak ring-width is one of the promising paleoclimate proxies in the tropical region. Tree-ring chronology spanning from 1840 to 2016 (177 years) was derived from seventy-six trees from Phrae Province, northern Thailand. A total of 141 core samples were cross-dated, a standardized master was constructed, and the tree residual master chronology was developed by ARSTAN program. The tree-ring chronology has a significant positive correlation with the monthly rainfall and relative humidity during the monsoon season (May - June). In addition, the growth of tree-ring width also significantly inversely correlated with Niño 3, Niño 3.4, and Niño 4 indices during the second half of the dry season (January - March). We reconstructed summer monsoon season (May - June) rainfall based on a linear regression model which explained 21.95% of the actual rainfall variance. The trend of the reconstructed rainfall record shows a decrease of 0.6 mm per decade and substantially showed four wet periods and five dry periods. These results suggest that this teak chronology has a good potential to be a high-resolution proxy for reconstructing the past local climate in northern Thailand.